Visual Repetition and Quantitative Descriptive Analysis of Visual Discourse in Environmental Activism Posters: The Work of Nobodycorp.org in the Bali Rejects Benoa Bay Reclamation - I Gusti Ngurah Tri Marutama; Bambang Sunarto; Bambang Sugiharto (INJECT (Interdisciplinary Journal of Communication), 2026)
This article examines twelve environmental activism posters from the "Bali Rejects Benoa Bay Reclamation" campaign (2014–2018) produced by Nobodycorp.org as a limited visual corpus within the communication system of the ForBALI movement. This study establishes the corpus as an object of analysis through scope limitation to maintain analytical rigor. This analysis integrates descriptive-quantitative mapping with critical discourse analysis through the tracking of visual relations, thereby structurally identifying ideological meanings. This procedure applies quantitative visual discourse methods through frequency distribution and co-occurrence networks, systematically detecting dominant elements. These findings indicate the red color system, the black color system, and the excavator image as the main elements, with the excavator appearing in 91.7% of the data. This analysis shows a relational intensity between the excavator and the red color of 0.92, and between the excavator and the black color of 0.74, thus forming a stable pattern of visual interconnection. These results demonstrate the stabilization of visual meaning through repeated relational grouping, so that signification does not depend on isolated symbolic units. This research formulates an operational model of visual meaning based on measurable relations through limited generalization, allowing visual communication studies to obtain replicable analytical instruments. This analysis shows the formation of ideological coherence through systematic visual organization, thereby articulating the framework of ecological conflict consistently. This analysis shows peripheral elements as low-connectivity components through relational measurement, thereby forming a structured asymmetry in the representation system. This research limits the analysis to a single producer corpus through data delimitation, so broad generalizations and reception dynamics are not covered.